COMPARATIVE STUDY FOR DIFFERENT PREVENTIVE METHODS FOR POSTPARTUM HEMORRHAGE (PPH) - ABBASI , M; SIDDIQUI , ES; GHAFFAR , S; HEMLATA , DR; JABEEN , N; QARSHI , W (Biological and Clinical Sciences Research Journal, 2023)
Different preventive methods have been used to reduce the incidence of PPH, but their efficacy, safety, and cost-effectiveness have not been well established. We conducted a comparative study to evaluate the effectiveness, side effects, and cost of different preventive methods for PPH. 120 patients at LUMHS from 2021 to 2022 were randomly assigned to receive one of four preventive methods: oxytocin, misoprostol, tranexamic acid, or prophylactic balloon catheterization. Data on the incidence of PPH, mean blood loss, need for additional interventions, and adverse events were collected and analyzed using logistic regression and ANOVA. The incidence of PPH was significantly lower in the tranexamic acid group (4%) and the prophylactic balloon catheterization group (6%) compared to the oxytocin group (16%) and the misoprostol group (14%). The mean blood loss was also significantly lower in the tranexamic acid and the prophylactic balloon catheterization groups than in the oxytocin and misoprostol groups. The need for additional interventions and adverse events were also significantly lower in the tranexamic acid and prophylactic balloon catheterization groups. Our study provides evidence to support tranexamic acid and prophylactic balloon catheterization as effective and safe preventive methods for PPH, with minimal side effects and low cost. Oxytocin remains a viable option for preventing PPH, but misoprostol should be used cautiously due to its higher incidence of adverse events.